(untitled) (Plant Tissue Culture and Biotechnology, 2019)
Carnation’s essential oil with high content of eugenol (monoterpenes) was extracted from carnation plant calli. Eugenol had antimicrobial effect and could be used to prolong the shelf life of fermented products as yoghurt. Eugenol in carnation essential oil was added to milk, at the percentages of (0.2, 0.4, 0.6, and 0.8 μl/ml milk, respectively before using the milk in the yoghurt manufacture. Results indicated that eugenol in carnation essential oil possessed good inhibitory effect against selected pathogenic bacterial strains at different concentrations, but had no inhibitory effect on Saccharomyces cerevisiae. Addition of carnation essential oil affected the pH and titratable acidity of the prepared yoghurt. Moreover, total solids, total protein and fat-to-dry matter records were slightly affected. The total viable counts, also, counts of yoghurt starter cultures and Lactobacillus acidophilus in yoghurt samples enhanced to become a maximum after 10 days of storage and reduced thereafter. Yeasts and molds, and coliform bacteria were not detected in the treated yoghurt. In different samples of yoghurt, yoghurt containing 0.6 μl/ml eugenol was the most acceptable organoleptically. It can be concluded that 0.6 μl/ml eugenol, can be applied to prolong yoghurt storage time for more than 15 days. Plant Tissue Cult. & Biotech. 29(1): 1-14, 2019 (June)